Thermal dehydration kinetics of non-crystalline manganese borate - Tugrul, Nurcan; Firat, Ebru; Kipcak, Azmi Seyhun; Yildirim, Meral; Senberber, Fatma Tugce; Derun, Emek Moroydor (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2020)
In this study, non-crystalline manganese tetrahydric orthoborate (MnH4(BO3)(2)) has been synthesized by using MnSO4 center dot H2O, NaOH and H3BO3 via hydrothermal method. The characterizations of the synthesized compounds have been conducted using X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). Thermal dehydration studies have been conducted using the thermogravimetric analysis (DTG/TG). From the XRD result, it is confirmed that amorphous manganese borate is synthesized and the corresponding characteristic borate vibration are observed in FTIR spectrum shows. A particle size distribution at the micron scale with partially agglomerated state is observed from SEM images. The thermogravimetric results show that dehydration process occurs between the temperatures of 40-270 degrees C in one-step reaction with average weight loss of 19.26%. Average activation energies have been determined by using the non-isothermal kinetics methods of Coats-Redfern, Horowitz-Metzger and Van-Krevelen and found as 37.83, 46.54 and 37.88 kJ mol(-1), respectively.
Keywords: Non-crystalline; Non-isothermal kinetics; Manganese borate; Coats-Redfern; Horowitz-Metzger; Van-Krevelen; CRYSTAL-STRUCTURE; Chemistry